THE FUNCTION OF INDONESIAN WOMEN COALITION (KPI) IN EFFORTS TO IMPROVE WOMEN LEADERSHIP IN BLITAR CITY - Dewi Frenti; Anam Miftakhul Huda (JARES (Journal of Academic Research and Sciences), 2017)
Women who have been used as the object of national development is considered to be anfair, due to the current conditions of women already have to be the perpetrators of the change. Their motion is limited in the domestic territory. Indeed, the normative idea contained in the 1945 Constitution has never been a record stating that there is no differentiate between men and women. Politic and election are clear to accommodate women to participate more broadly. The research objectives is to know: 1) kinds of programs of KPI Blitar 2) Supporting factors and inhibitors program of KPI Blitar. This research uses a qualitative approach that describes all the activities of KPI Blitar related to efforts of women empowerment in Blitar. The results of this research indicates: 1) The role of KPI Blitar city in Improving Leadership of female autonomy. 2) Supporting factors of KPI Blitar city which cooperate with government institution, independently, local and national. Internal and external constraint factors lead many women to become activists of rights struggle, and tend to rely on men ability. Key words: Indonesian Women Coalition (KPI), Patriakhi, Domestik. Received: 12 August, 2017; Accepter: 10 September, 2017